Microlending: Is There Demand for Such Loans in Germany? - Alexander S. Kritikos; Christoph Kneiding (Weekly Report, 2010)
A lack of financial means is viewed as a key reason why small businesses fail. Therefore, also in Germany several institutions tried to establish microloans as a financing tool. A first empirical study, building a benchmark for similar studies in Western Europe, shows that about 15 percent of all self-employed individuals would be interested in getting access to microloans. The study also demonstrates that these financial needs exist in target groups different from what was previously expected at least in Germany. Rather than offering microloans to business founders, they should be offered to existing small business owners in specific sectors. In addition, in order to be accepted by entrepreneurs, access to microloans must be available rapidly, with short repayment periods.
Keywords: G21; D12; M31; 330; Entrepreneurship; Microlending; Market research